Influence of flood control structures on the water level in the downstream of the Saigon – Dong Nai river system - I. M. Markova; Phan Khanh Khanh (Vestnik MGSU)
Introduction. Ho Chi Minh City, the largest city in Vietnam, located in the lower reaches of the Saigon – Dong Nai river system, is facing increasingly severe flooding due to changes in river flow and water levels. This article presents the results of a study to assess the impact of hydraulic structures located in the upper reaches on the water level in the lower reaches of the SG – DN river.Materials and methods. To assess the impact of upstream reservoirs and flood control structures on the water level in the lower reaches of the SG – DN river, hydrological data of the river network were collected and a hydraulic model was developed based on a digital elevation model (DEM) using the software package Mike 11, Mike 21 and Mike Flood.Results. The water level of the Saigon River from the upper reaches to the Thu Dau Mot measuring station directly depends on the Dau Tieng reservoir, and the Tri An reservoir directly affects the water level in the river section from behind the Tri An dam to the Dong Nai section in the Tam An – Long Phuoc area.Conclusions. In the sections of the Saigon and Dong Nai Rivers less affected by the two upstream reservoirs, it is necessary to develop preventive measures to supply sufficient fresh water to meet the needs of the population and industries. In areas prone to flooding and underflooding as a result of the operation of floodgates, it is also necessary to reconstruct hydraulic structures (raise foundation level, expand drainage systems, build reservoirs to collect flood water etc.).